Hepatitis D virus antibodies and liver function profile among patients with chronic hepatitis B infection in Abuja, Nigeria - Lukman O Abdulkareem; Dennis A Ndububa; Augustine O Uhunmwangho; Thahir Yunusa (Journal of Infection in Developing Countries)
Introduction: Hepatitis D virus (HDV) is a satellite virus of hepatitis B virus (HBV). An estimated 5% of HBV infected individuals worldwide have HDV infection. There is paucity of studies in Nigeria on the burden of HDV infection. This study aimed at determining the prevalence rate of HDV antibodies among individuals with chronic hepatitis B (CHB) infection and comparing the liver function test (LFT) and disease severity among the anti-HDV positive (anti-HDV+) and anti-HDV negative (anti-HDV-) individuals.